Incidence and associated risk factors of LV clot among patients with myocardial infarction of Urmia Seyyed-O- Shohada heart center - Alireza Rostamzadeh (Journal of Global Pharma Technology, 2016)
BackgroundBased on previous experiments with a limited number of samples, it seems that the use of anticoagulants(heparin or subcutaneous high dose heparin) reduces by 50%of the progression of left ventricular embolism.In this study, we determined to investigate the incidence and factors associated with left ventricular thrombusin patients with acute myocardial infarction admitted to Seyyed-al- shohada University Hospital.MethodsIn this analytic cohort study, patients with myocardial infarction were included and risk factors of LV clotfollowing of myocardial infarction as, diabetes mellitus, smoking, hypertension, dyslipidemia, higher age,gender, extent of cardiac involvement, LV diastolic dysfunction and reperfusion were evaluated. Also, otherechocardiographic parameters as LV size, LV systolic and diastolic dysfunction, assessed and recorded in acheck list. Finally effect of each factor on incidence of LV clot was evaluated separately.ResultsIn our study, we found no significant association between underlying disease, diabetes, history of prior MI,history of hyperlipidemia, smoking and SK infusion, but there was a significant association between the typeof MI and clots in the left ventricle. In this study, we found no significant association between the incidence ofthrombus within the left ventricle and Primary PCI. Also receiving Heparin and/or Enoxaparin and Metoral arenot significantly associated with LV clots. However, there is no significant association between LV size andcount of involved leads in the incidence of left ventricular thrombus.Conclusion: Finally, according to the results of the study it can be said that the time from onset of the pain untilrevascularization in the hospital, had an important role in preventing LV clots and the outcomes of the patient.Key words: Incidence, risk factors, LV clot, myocardial infarction.